FAKTOR –FAKTOR YANG MEMPENGARUHI NIAT PADA PERILAKU NASABAH MENABUNG DI PERBANKAN SYARIAH DENGAN AGAMA SEBAGAI VARIABEL KONTROL - Aglis Andhita Hatmawan; Any Widiasmara (Universitas PGRI Madiun, 2016)
This study aims to determine the factors that influence the saving behavior of muslim community to use the Islamic banking in Madiun. Data collection was done by distributing questionnaires. A total of 360 questionnaires were distributed and the total of 320 questionnaires were returned Analyses were performed with PLS method. The results analyzes showed that attitude, Perceived bihavior control and subyek norm shows a influence is significant on intention. as well as the variables religiosity are taken as moderation couldn’t explain the relationship between and intention on saving behavior in Islamic banks. The study has implications for Islamic bank that can appropriately target the customers using islamic bank selection determinants that are valued by the customers. This paper is one of the few that has used a quanlitative approach to study saving behavior for Islamic banking. Furthermore, the paper employs this methodology in the context of madiun city, which enriches the studies done in this context and area.